PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SD MUHAMMADIYAH KARUWISI MAKASSAR - Anisa Almaimuna; Munirah; Anzar (STKIP Subang, 2026)
The problem addressed in this study is the low speaking skills of fourth-grade students at SD Muhammadiyah Karuwisi Makassar. This study aims to improve students’ speaking skills by using the Round Robin learning model in fourth-grade students at SD Muhammadiyah Karuwisi Makassar. This research employs both qualitative and quantitative approaches with a Classroom Action Research (CAR) design. The subjects of this study were seven fourth-grade students. The data collection techniques used were observation, tests, and documentation. The results of the study indicate that the implementation of the Round Robin learning model is able to improve the speaking skills of fourth-grade students at SD Muhammadiyah Karuwisi Makassar. The improvement in speaking skills can be seen from the achievement of the research success indicators, marked by an increase in the percentage of students’ learning mastery in each cycle. The percentage of learning mastery in Cycle I was 43%, and it increased to 100% in Cycle II.